Influence of Dunes on Channel‐Scale Flow and Sediment Transport in a Sand Bed Braided River. Issue 11 (17th November 2020) - Unsworth, Christopher A.; Nicholas, Andrew P.; Ashworth, Philip J.; Best, James L.; Lane, Stuart N.; Parsons, Daniel R.; Sambrook Smith, Gregory H.; Simpson, Christopher J.; Strick, Robert J. P.
Abstract: Current understanding of the role that dunes play in controlling bar and channel‐scale processes and river morphodynamics is incomplete. We present results from a combined numerical modeling and field monitoring study that isolates the impact of dunes on depth‐averaged and near‐bed flow structure, with implications for morphodynamic modeling. Numerical simulations were conducted using the three‐dimensional computational fluid dynamics code OpenFOAM to quantify the time‐averaged flow structure within a 400 m × 100 m channel using digital elevation models (DEMs) for which (i) dunes and bars were present within the model and (ii) only bar‐scale topographic features were resolved (dunes were removed). Comparison of these two simulations shows that dunes enhance lateral flows and reduce velocities over bar tops by as much as 30%. Dunes influence the direction of modeled sediment transport at spatial scales larger than individual bedforms due to their effect on topographic steering of the near‐bed flow structure. We show that dunes can amplify, dampen, or even reverse the deflection of sediment down lateral bar slopes, and this is closely associated with 3‐D and obliquely orientated dunes. Sediment transport patterns calculated using theory implemented in depth‐averaged morphodynamic models suggest that gravitational deflection of sediment is still controlled by bar‐scale topography, even in the presence of dunes. However, improved parameterizations of flow and sediment transport in depth‐averaged morphodynamic models are needed that account for the effects of both dune‐ and bar‐scale morphology on near‐bed flow and sediment transport. Key Points: 3‐D CFD is used to quantify the flow structure over dunes superimposed upon large‐scale alternate bars in a natural river Net influence of dunes is to enhance lateral flows and reduce velocities over bar tops by as much as 30% Dunes can amplify or dampen the deflection of sediment down lateral bar slopes